WILLINGNESS TO PAY RUMAH TANGGA DALAM MEMBAYAR BIAYA PENDIDIKAN MENENGAH UNGGULAN DI KOTA MALANG - Rosyadi, Muhammad Irfan (FKIP Universitas Lampung, 2016)
Households Willingness to Pay of Excellent Secondary Education Cost In Malang City. The importance of education to economic development and the understanding of households determine the educational services, these makes excellent secondary educational institutions in Malang greatly demanded, but the willingness to pay the cost of education questionable. This study used primary data from a questionnaire completed by 150 respondents, and then analyzed by multiple regression method to measure the value of willingness to pay as well as the dependent variables influenced. The study showed that an average household are less willing to pay the cost of excellent secondary education. Income, number of dependents, education and access had a significant effect. Keywords: willingness to pay, household, excellent secondary education DOI: http://dx.doi.org/10.23960/jpp.v6.i2.201601